Why People Forgo Healthcare in France: A National Survey of 164 092 Individuals to Inform Healthcare Policy-Makers - Najeh Daabek; Sébastien Bailly; Alison Foote; Philippe Warin; Renaud Tamisier; Hélèna Revil; Jean-Louis Pépin (Kerman University of Medical Sciences, 2022)
Background  Even in countries having nearly universal healthcare provision some individuals forgo or postpone healthcare to which they are entitled. Socioeconomic and geographic inequalities can make access to healthcare difficult for some people, such that they fail to seek it, particularly if they deem the type of care as non-essential. The need to pay at the point of care, the complexity and cost of top-up health insurance, and delays or only partial reimbursement can discourage take-up of care. This can affect the general health of the population.Methods  To estimate the rate of forgoing healthcare in the general French population, between 2015 and 2018 we conducted a nationwide cross-sectional survey of individuals visiting French primary healthcare insurance agencies (Caisse Primaire d'Assurance Maladie, CPAM). We asked whether the person had foregone or postponed healthcare in the last 12 months, if so the types of healthcare forgone or put-off, and reasons. Individuals were stratified by the type of complementary (top-up) health insurance they had.Results  Out of 164 092 individuals who responded, 158 032 were included in the analysis. Respondents had either private complementary (top-up) insurance (60%), top-up insurance subsidized by the state (29%), or no top-up health insurance (11%). Forgoers (n=40 115; 25.4%) most often lived alone (with or without children), were unemployed, and/ or female. Dental care (54%) and consultations with ophthalmologists, gynaecologists and dermatologists (41%) were most commonly forgone. The reasons were: inability to advance payment and/or to pay the uninsured part (69%), time constraints and difficulty in obtaining appointments (26%).Conclusion  We present a snapshot of forgoing healthcare in a developed country, highlighting the need for continuing review by policy-makers of payment regimens, insurance cover, availability and accessibility. While initiatives have already emerged from the results, further reforms are needed to address the problem of people forgoing preventative or perceived non-urgent healthcare, particularly for disadvantaged subgroups.